Poor sleep Quality and Obstructive Sleep Apnea are Associated with Maternal Mood, and Anxiety Disorders in Pregnancy - Rubio, Elia (2022)
Background: Previous studies suggest sleep quality and obstructive sleep apnea (OSA) may be associated with psychiatric symptoms, including depression, anxiety, and posttraumatic stress disorder (PTSD). However, few studies have examined the relationship between sleep quality and OSA with maternal psychiatric symptoms during pregnancy, a state of vulnerability to these disorders. Objective: The objective of our study is to examine the association between poor sleep quality and sleep apnea with antepartum depression, anxiety, and PTSD among pregnant women. Methods: A cross-sectional study was conducted among women seeking prenatal care in Lima, Peru. Sleep quality was measured using the Pittsburgh Sleep Quality Index, and the Berlin questionnaire was used to identify women at high risk for OSA. Depression, generalized anxiety, and PTSD symptoms were measured using the Patient Health Questionnaire-9, Generalized Anxiety Disorder Assessment, and PTSD Checklist – Civilian Version. Multivariate logistic regression procedures were used to estimate adjusted odds ratios (aOR) and 95% confidence intervals (95% CI). Results: Approximately 29.0X% of women had poor sleep quality, and 6.2% were at high risk for OSA. The prevalence of psychiatric symptoms was high in this cohort with 25.1%, 32.5%, and 30.9% of women reporting symptoms of antepartum depression, antepartum anxiety, and PTSD, respectively. Women with poor sleep quality had higher odds of antepartum depression (aOR = 3.28; 95%CI: 2.64–4.07), generalized anxiety (aOR = 1.94; 95%CI: 1.58–2.38), and PTSD symptoms (aOR = 2.81; 95% CI: 2.28–3.46) as compared with women who reported good sleep quality. Women with a high risk of OSA had higher odds of antepartum depression (aOR = 2.36; 95% CI: 1.57–3.56), generalized anxiety (aOR = 2.02, 95% CI: 1.36–3.00), and PTSD symptoms (aOR = 2.14; 95%CI: 1.43–3.21) as compared with those with a low risk of sleep apnea. Conclusions: Poor sleep quality and high risk of OSA are associated with antepartum depression, generalized anxiety, and PTSD symptoms among pregnant women. Further characterizations of the associations of these prevalent sleep, mood, and anxiety conditions among pregnant women could aid in evaluating and delivering optimal perinatal care to women with these comorbidities.